A personal tour of cultural heritage for deaf museum visitors - Constantinou, Vaso; Loizides, Fernando; Ioannou, Andri (My University, 2016)
This paper describes the first milestone and results of an ongoing project involving the implementation and pilot testing of an application aiming to promote cultural heritage and dissemination of information with the use of interactive small screen technology. The bespoke application was designed for deaf visitors to enable a museum experience without the support of a physical sign language interpreter. The application was pilot tested in the Pattichion Municipal Museum in Cyprus. Our findings showed high levels of user satisfaction and usefulness of the application in allowing deaf museum visitors to have an enjoyable tour, using their mobile devices as the only means of support.
Keywords: Accessibility; Cultural heritage; Deaf; Hard of hearing; Hearing disability